Experiences of key populations in getting and sharing HIV and AIDS-related information: A descriptive phenomenological study - Pahadi, Toya Nath (Journal of Health Promotion, 2022)
Despite the long-running targeted communication programs, the concentrated HIV epidemic in key populations has not declined as expectedin Nepal.In this context, the present descriptive phenomenological study was carried out in Nepalgunj Submetropolitan City to explore the experiences of key populations in getting and sharing HIV and AIDS-related information. In-depth interviews were carried out with nine participants selected through snowball sampling from sexual minority people, and female sex workers. Colaizzi’s descriptive phenomenological analysis method was adopted in data analysis. Participants were increasingly using digital means of communication. Peer approach was experienced as more confidential and training in drop-in-center a friendly mode of communication. Experiences of embarrassment, stigma, and discrimination were also prevalent. The findings of this study indicate HIV communication needs to be easily accessible, confidential, and friendly.